THE IMPLEMENTATION OF THE PESANTREN CURRICULUM ON THE LEARNING OUTCOMES OF SANTRI IN INDONESIA: A SYSTEMATIC LITERATURE REVIEW - Khairul Anwar; M.Harisul Wahyi A. Fakar; Lisma Tiarawati; Mega Setiawati; Nandini Titi Rahayu; Melsa Oktapia (Institut Agama Islam Negeri (IAIN) Curup, 2026)
This study analyzes the implementation of various Islamic boarding school (pesantren) curriculum models and their impact on students’ learning outcomes in Indonesia using a Systematic Literature Review (SLR) approach. Twenty-one selected articles published between 2021 and 2025 were examined based on curriculum characteristics, learning outcome domains, and supporting and inhibiting factors. The findings indicate that pesantren curricula—including integrative curricula, classical kitab kuning, tahfidz programs, specialization (takhassus), and mu’adalah—positively contribute to students’ learning outcomes, particularly in the cognitive domain, followed by psychomotor and affective aspects. Successful curriculum implementation is supported by teachers’ competence, a conducive pesantren environment, traditional pedagogical methods, and effective curriculum management. However, several challenges persist, including students’ varied initial abilities, limited facilities, insufficient teacher training, and difficulties in curriculum adaptation. Overall, the study highlights that the effectiveness of pesantren curricula relies not only on curriculum design but also on the readiness of human resources and strong institutional support to ensure sustainable learning processes.